Designing and validating the friendship quality on social network sites questionnaire. (September 2018) - Verswijvel, Karen; Heirman, Wannes; Hardies, Kris; Walrave, Michel
Abstract: Social network sites (SNSs) provide adolescents with the opportunity to expand their social circle, which is associated with increased social capital. However, the social capital adolescents built depends on the quality of their friendships on SNSs. As no instruments are available to capture the quality of friendships on SNSs, this study designed and validated the Friendship Quality on Social Network Sites questionnaire ( FQSNS-questionnaire) . The questionnaire consists of five dimensions: satisfaction, companionship, help, intimacy, and self-validation. Explorative and confirmative factor analyses were applied on data of 1.695 friendships (i.e., offline-to-online, online-to-offline, and online friendships) gathered from 1.087 adolescents. Results pointed to a five-factor solution, applicable to any kind of friendship on SNSs and reflecting the proposed five dimensions of friendship quality. Multiple group confirmatory factor analyses supported measurement invariance across younger and older adolescents, and across boys and girls, at the levels of equal factor structure and loadings. Cronbach's alphas indicated a good internal consistency of each dimension. Correlation analysis indicated that the dimensions were strongly correlated to each other, which is unsurprising because they reflect the overall friendship quality. Based upon these results, we can conclude that dimensions of friendship quality can validly and reliably be assessed using the FQSNS-questionnaire . Highlights: The Friendship Quality on Social Network Sites questionnaire ( FQSNS-questionnaire ): Measures five quality dimensions of friendships on social network sites. Is applicable to any kind of friendship on social network sites. Has equal factor structure for boys and girls, and younger and older adolescents. Has equal factor loadings for boys and girls, and younger and older adolescents.